Divine text and Ijtihad: complementation or conflict - Moustapha, Sano Koutoub (s.n, 2012)
This study investigated the nature of relationship between divine text and Ijtihad. It also discussed the continuous efforts of those scholars in defining and determining the said relationship. Furthermore, the study stressed the urgent need for avoiding any form of conflict between the divine text Ijtihad. Thus both of them need each other. They only conflict in the eyes of those people who lack of a proper understanding of the nature and type of each of them